The Effect of Company Performance on Underpricing Level IPO Shares on the Indonesia Stock Exchange for the Period 2013- 2023 - PRADNYANA, Komang Wisnu Aria; ERAWATI, Ni Made Adi (PT Keberlanjutan Strategis Indonesia, 2024)
The purpose of this study was to examine the effect of profitability, solvency, company size, and company age on the level of underpricing of IPO shares on the Indonesia Stock Exchange for the period 2013- 2023. Underpricing is the difference between the IPO stock offering price and the market price when the shares are first traded on the market. This study aims to examine the effect of profitability, solvency, company size and company age on the level of underpricing of IPOshares on the IDX for the period 2013-2023. The sample of this study was 376 using purposive sampling. Data collection techniques using non-participant observation methods. The data analysis technique used is the Structural Equation Model (SEM) using Partial Least Square (PLS). Research data is processed using Smart-PLS version 4 software by evaluating the inner model and bootstrapping. The results of this study indicate that profitability, solvency, company size and company age have a negative effect on the level of underpricing of IPO shares on the IDX for the period 2013-2023. This means that the better profitability, solvency and company size owned can reduce the level of underpricing of IPO shares. Companies that have been established for a long time can also reduce the level of underpricing of IPO shares on the IDX for the 2013-2023 period.